Legal Regulation of National Security in Ukraine: Strategies and Challenges - Honcharuk, Vladyslav; Karpenko, Mykola; Prytula, Anatolii; Fierieva, Natalia; Andrushko, Oleksandr (NAJAHA, 2025)
This article aims to analyse the key challenges facing the legal regulation of Ukraine’s national security sector amidst Russian aggression, to identify current strategies for national security formation, and to develop key recommendations for optimising the regulatory and legal framework. This research is a qualitative study with a systematic approach.The PRISMA approach was utilised for the collection of academic literature. Applying inclusion and exclusion criteria, 44 relevant academic publications were retained. The collected material was processed using comparison, systematisation, and analysis methods. The study shows that Russia's aggression against Ukraine has exposed significant weaknesses in the national and international security systems, prompting Ukraine to reform its legal framework and security strategy, including harmonization with NATO and EU standards. Key challenges identified include cyber threats, the migration crisis, and hybrid threats such as propaganda and foreign intelligence activities. The study emphasizes the need for updating national legislation, improving interagency coordination, and integrating the experiences of other countries such as the United Kingdom, the United States, and Poland. Key recommendations include optimizing the legal framework through international standards, civil society participation, and global strategic partnerships to ensure Ukraine's adaptive and effective national security. The originality of the paper lies in the analysis of modern challenges and prospects for the legal regulation of national security of Ukraine in the context of Euro-Atlantic integration and global transformations of the security environment. The limitations of the study are related to the dynamism of the regulatory framework and rapid changes in the field of cybersecurity, which requires further research to adapt the legal field to new threats.